2013
DOI: 10.11646/zootaxa.3709.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Four new species of coral gobies (Teleostei: Gobiidae: Gobiodon), with comments on their relationships within the genus

Abstract: Four new species of the coral-associated gobiid genus Gobiodon were discovered in the Red Sea. Although several of these species are common not only in the Red Sea but also in the Indian and western Pacific Ocean, they have not been described before. Detailed descriptions of the four species are based on morphological and molecular genetic (mitochondrial 12s and 16s rRNA) investigations. The new species, like most species of the genus, lack scales and have species-specific life colouration. Gobiodon bilineatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…peguense is more highly differentiated than the other two subspecies. Although this has previously been suggested, the complete 13 PCGs comparison can obtain more genetic information than single gene fragments, and thus reduces the effects of specific mitochondrial gene fragments [56]. The analysis presented, in combination with the species of 13 PCGs, showed that the genetic distances between P .…”
Section: Resultsmentioning
confidence: 96%
“…peguense is more highly differentiated than the other two subspecies. Although this has previously been suggested, the complete 13 PCGs comparison can obtain more genetic information than single gene fragments, and thus reduces the effects of specific mitochondrial gene fragments [56]. The analysis presented, in combination with the species of 13 PCGs, showed that the genetic distances between P .…”
Section: Resultsmentioning
confidence: 96%
“…Molecular tools are proving useful for the identification of cryptic lineages in endemism hotspots such as Hawai'i (Randall et al ., ), the Marquesas Islands (Szabo et al ., ) and the Red Sea (Randall & DiBattista, ). In the Red Sea, only 10% of the new species descriptions listed in Table were corroborated using molecular data, but this includes three new species of fish (DiBattista et al ., ; Herler et al ., ; Koeda et al ., ) and a coral (Terraneo et al ., ). As molecular tools are applied more broadly, endemism in the region will continue to rise.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 97%
“…Among all molecular markers, the mtDNA COI and cyt b genes have been the most frequently used (Yang et al 2016;Han et al 2019;Hsu et al 2020;Ju et al 2021). In addition, some studies have used mtDNA rRNA (12S and 16S) sequences to resolve phylogenetic relationships and taxonomy (Byrne et al 2010;Herler et al 2013;Zheng et al 2016). However, the results of pairwise p-distances based on 16S rRNA and cyt b genes differed in this study (Table 6).…”
Section: Molecular Tool Assessmentmentioning
confidence: 73%